Prosody in the Auditory and Visual Domains: A Developmental Perspective - Esteve-Gibert, Núria; Guellaï, Bahia (Frontiers in Psychology, 2018)
The development of body movements such as hand or head gestures, or facial expressions, seems to go hand-in-hand with the development of speech abilities. We know that very young infants rely on the movements of their caregivers’ mouth to segment the speech stream, that infants’ canonical babbling is temporally related to rhythmic hand movements, that narrative abilities emerge at a similar time in speech and gestures, and that children make use of both modalities to access complex pragmatic intentions. Prosody has emerged as a key linguistic component in this speech-gesture relationship, yet its exact role in the development of multimodal communication is still not well understood. For example, it is not clear what the relative weights of speech prosody and body gestures are in language acquisition, or whether both modalities develop at the same time or whether one modality needs to be in place for the other to emerge. The present paper reviews existing literature on the interactions between speech prosody and body movements from a developmental perspective in order to shed some light on these issues.